Media Sosial Instagram Influencer Adnan Abdillah sebagai Media Promosi Brand Fashion - nisrina, shypa; Detya Wiryany; Ahmad Taufiq Maulana Ramdan, (Jurnal Inovasi Komunikasi, 2024)
This research aims to educate social media users to be positive if used properly and correctly, by following the current fashion developments can produce useful ones, current technology is developing more rapidly can provide information with various purposes such as exchanging information, people are able to interact without the need for face-to-face. Currently, social media is not only exchanging information but can be used as a marketing tool, advertising in social media is widely used today. Because of this, influencers have emerged, namely social media users with a large number of followers or followers, not all can be called influencers, only some people who have uniqueness in creating content or posting unique things, as nowadays most influencers create content using unique and trendy fashion to attract the attention of their followers.